Evaluasi Komunikasi Lingkungan Dalam Pengelolaan Ekosistem Gambut di Kelurahan Teluk Meranti, Pelalawan - Pratiwi, Rosi; Firdaus, Muhammad; Arifudin, Arifudin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This research was motivated by the large number of forest and peatland fires that occurred in 2019 in Teluk Meranti District. One of the causes of the Hitan and peatland fires is human factors. Lack of understanding of humans working around peatlands. This research aims to analyze the evaluation of environmental communication in managing the peat ecosystem in Meranti Bay. This study used descriptive qualitative method. Data collection techniques are carried out through interviews, observation and documentation. Data analysis techniques begin with data collection, data reduction, data presentation, ending with drawing conclusions. The results of this research indicate that the Evaluation of Environmental Communication in the management of the Peat Ecosystem in Meranti Bay has gone well. Evaluation includes research carried out, then evaluation which includes communication development, namely Focus Group Discussions, Community Responses.